Eric Voegelin wobec narodowego socjalizmu. Próba filozoficzno-religijnej interpretacji zjawiska - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The article is devoted to Eric Voegelin’s efforts at the interpretation of National Socialism. He was a prominent Austrian historian of philosophy who escaped from the Third Reich to the United States. Voegelin’s philosophy grew out of the crisis of classical philosophy and from its confrontation with modernist thought out of which National Socialism itself also sprouted. Nevertheless this author analyzed the phenomenon of Fascism in only one book, namely Hitler und die Deutschen. There are many indications that Voegelin believed that his work was truly groundbreaking as far as the phenomenon of Nazism is concerned. The fact that its reception was not particularly favorable was for him a source of deep anguish and disappointment. The article encompasses the analysis of aforementioned book and its comparison with other works by Voegelin. According to the author of this text, the failure of the Austrian historian’s book was a result of its banality. Voegelin made a quite a simplistic claim that German people at large are responsible for the emergence of Fascism.Although his political preferences ought to be described as conservative, he still maintained that Catholic and Evangelical Churches also can be blamed for excesses of National Socialism this opinion disqualified his book among right-wing readers. At the same time representatives of leftleaning audience refused to read and acknowledge Voegelin’s book due to the author’s generally right-wing viewpoint.
Keywords: National Socialism; Voegelin, Eric (1901-1985); Fascism; Hitle, Adolf (1889-1945)